A study of Yemeni EFL instructors’ perceptions on the role of ICTs in developing students’ communicative competence - Aref Nassi Abdu Nasser; Wagdi Rashad Ali Bin-Hady; Sabri Thabit Saleh Ahmed (Universitas Kuningan, 2020)
This paper aims at exploring Yemeni instructors' perceptions on the role that ICTs play in developing EFL students' communicative competence components. The study pursued a quantitative research design as a method for data collection. A closed-ended questionnaire was constructed, developed, and shared with 60 Yemeni EFL instructors using Google forms. The validity of the questionnaire was checked by referees whereas Cronbach's Alpha was run to measure the questionnaire reliability (R=.86). SPSS 21st edition was used to analyse the data. The study revealed that Yemeni EFL instructors have positive perceptions on the role of using ICTs in developing students' communicative competence. The findings also reported no statistically significant differences in the instructors' perceptions of ICTs that can be found across the four components of communicative competence. Moreover, it was revealed that there are no statistically significant differences in the instructors' perceptions that can be attributed to gender across the components. This study encourages EFL instructors to help their students to use the ICT tools in developing their communicative competence.